Glued-in basalt FRP rods under combined axial force and bending moment: An experimental study. (15th February 2018) - O'Neill, Caoimhe; McPolin, Daniel; Taylor, Su E.; Martin, Tony; Harte, Annette M.
Abstract: Glued-in rods have potential for use as moment-resisting connections in timber structures. There has been minimal research to date conducted on the performance of glued-in rods acting under both axial force and moment. The influence of increasing embedded length of the glued-in rod on the strength of the system was assessed using a pull-bending test which subjected the connection to this force combination. The longest length (600 mm) had a pull-out capacity 213% greater than the shortest (80 mm). To reduce instances of splitting in the timber end distance was varied. Optimum end distance of 42 mm (3.5 dr ) was identified with further increase having minimal impact upon overall strength.